FENOMENA BAJU THRIFT PADA MAHASISWA DI BENGKULU - Widanti, Afrima; Ilsya Hayadi; Febzi Fiona (UNIB Press, 2023)
This study aims to determine the factors that cause the thrifting clothing phenomenon in Bengkulu to increase. Many factors, such as internal and external factors, influence consumers' decisions to purchase clothing. One of the internal factors is a lifestyle where someone always wants to look fashionable, influencing consumers to buy thrifting clothes. External factors, such as low prices and good product quality, even though they are used, are some of the factors that influence purchasing decisions. The analytical method used is non-probability sampling, namely purposive sampling—hypothesis analysis using multiple linear regression. The unit of analysis is students in Bengkulu. One hundred forty-seven questionnaires can be processed. The study found that lifestyle, price, and product quality influence purchasing thrifting clothing. The better the quality of the product, the lifestyle of someone who is fashion, and the affordable price, the higher the decision to buy thrifting clothes